Experiences of Parents in Modular Distance Learning Delivery - Real, Don Vicente C.; Aniñon, Elsie C.; Lim, Ninotchka M.; Resoor, Nonale Q.; Englis, Andrea Luz (European Journal of Applied Sciences, 2023)
This study aimed to explore the experiences of the twenty-seven (27) parents of the Grade six learners, as “More Knowledgeable Others” toward Modular Distance Learning Delivery at Cantilo Elementary School, Pamplona 1, City Schools Division of Tanjay. The qualitative method through phenomenological research was used. It is the method of discovering and structuring the meaning of human incidents through interviews with people involved in the real-life experience [1]. Purposive sampling was used as a sampling technique to recruit participants who can provide in-depth and detailed information about the phenomenon under investigation. Findings revealed that the 27 parents have expressed their insights and suggestions in support of the continuous delivery of modular distance learning in the School Year 2021-2022. Although there were some negative suggestions, despite the minority in scope these deserved the attention of all the stakeholders both in the school and the local government. The majority of the parent-respondents embraced and supported the modular distance learning modality so that the education of their children could be continued, facilitated, and assessed both by the teachers and parents. However, continuous assistance (material and non-material) from barangay officials and LGU officials has always been appreciated. Should the MDL be continued in the upcoming school years, the parents have expressed their all-out support as long as they will continually be guided and assisted by the school teachers and officials regarding the proper procedures for handling their children while learning at home.